Dihomooxacalix[4]arene-Based Fluorescent Receptors for Anion and Organic Ion Pair Recognition - Miranda, Alexandre S. (Molecules, 2020)
Fluorescent dihomooxacalix[4]arene-based receptors 5a–5c, bearing two naphthyl(thio)ureido groups at the lower rim via a butyl spacer, were synthesised and obtained in the cone conformation in solution. The X-ray crystal structures of 1,3- (5a) and 3,4-dinaphthylurea (5b) derivatives are reported. Their binding properties towards several anions of different geometries were assessed by (1)H-NMR, UV-Vis absorption and fluorescence titrations. Structural and energetic insights of the naphthylurea 5a and 5b complexes were also obtained using quantum mechanical calculations. The data showed that all receptors follow the same trend, the association constants increase with the anion basicity, and the strongest complexes were obtained with F(−), followed by the oxoanions AcO(−) and BzO(−). Proximal urea 5b is a better anion receptor compared to distal urea 5a, and both are more efficient than thiourea 5c. Compounds 5a and 5b were also investigated as heteroditopic receptors for biologically relevant alkylammonium salts, such as the neurotransmitter γ-aminobutyric acid (GABA·HCl) and the betaine deoxycarnitine·HCl. Chiral recognition towards the guest sec-butylamine·HCl was also tested, and a 5:2 selectivity for (R)-sec-BuNH(3)(+)·Cl(−) towards (P) or (M) enantiomers of the inherently chiral receptor 5a was shown. Based on DFT calculations, the complex [(S)-sec-BuNH(3)(+)·Cl(−)/(M)-5a] was indicated as the more stable.